2010
DOI: 10.1111/j.1600-079x.2010.00831.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin protects steatotic and nonsteatotic liver grafts against cold ischemia and reperfusion injury

Abstract: :  Chronic organ‐donor shortage has required the acceptance of steatotic livers for transplantation purposes despite the higher risk of graft dysfunction or nonfunction associated with the cold ischemia–reperfusion injury. This study evaluated the use of melatonin as an additive to Institute Georges Lopez (IGL‐1) solution for protecting nonsteatotic and steatotic liver grafts against cold ischemia–reperfusion injury. In the current investigation, we used an ex vivo isolated perfused rat liver model. Steatotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 59 publications
(95 reference statements)
1
73
0
Order By: Relevance
“…Twenty-seven studies utilizing the thiobarbituric acid reactive substances assay showed significantly increased levels of MDA in steatotic livers post-IRI [20,21,23,25,28,32,34,38,40,44,46,48,52,54,55,57,[61][62][63]69,[71][72][73][75][76][77][78] while Nakano and colleagues [17] reported similar levels of perfusate MDA to that seen from lean livers. Serviddio et al [47] also reported a significant increase in mitochondrial 4-hydroxy-2-nonenal-protein adducts post-IRI in steatotic livers.…”
Section: Lipid Peroxidationmentioning
confidence: 95%
See 4 more Smart Citations
“…Twenty-seven studies utilizing the thiobarbituric acid reactive substances assay showed significantly increased levels of MDA in steatotic livers post-IRI [20,21,23,25,28,32,34,38,40,44,46,48,52,54,55,57,[61][62][63]69,[71][72][73][75][76][77][78] while Nakano and colleagues [17] reported similar levels of perfusate MDA to that seen from lean livers. Serviddio et al [47] also reported a significant increase in mitochondrial 4-hydroxy-2-nonenal-protein adducts post-IRI in steatotic livers.…”
Section: Lipid Peroxidationmentioning
confidence: 95%
“…Eight of the 63 studies reported HO-1 levels in steatotic livers. Four studies reported a greater increase in HO-1 levels in steatotic livers post-warm IRI [20,21,31,35] whereas in cold PRI, 2 studies showed similar increase in HO-1 levels in both types of liver [69,74] and another two studies showed decreased HO-1 protein levels in steatotic livers [60,76].…”
Section: Insulin-like Growth Factormentioning
confidence: 99%
See 3 more Smart Citations